2012
DOI: 10.1100/2012/926310
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Mechanisms for the Dominant Rainfall Mode over Zimbabwe Relative to ENSO and/or IODZM

Abstract: Zimbabwe's homogeneous precipitation regions are investigated by means of principal component analysis (PCA) with regard to the underlying processes related to ENSO and/or Indian Ocean Dipole zonal mode (IODZM). Station standardized precipitation index rather than direct rainfall values represent the data matrix used in the PCA. The results indicate that the country's rainfall is highly homogeneous and is dominantly described by the first principal mode (PC1). This leading PC can be used to represent the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(38 reference statements)
3
15
0
Order By: Relevance
“…Our results are in line with other studies that found ENSO-and IOD-rainfall-teleconnections across eastern and southern Africa (Li et al, 2013;Manatsa & Mukwada, 2012;Saji et al, 1999;Tierney, Smerdon, Anchukaitis, & Seager, 2010). Hence, examining the influence of ENSO and IOD on eastern Africa rainfall is vital to improve the understanding of mechanisms affecting regional weather conditions and the extent of global weather teleconnections.…”
Section: Remote Climate Forcing Of Rainfall On the Bluesupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are in line with other studies that found ENSO-and IOD-rainfall-teleconnections across eastern and southern Africa (Li et al, 2013;Manatsa & Mukwada, 2012;Saji et al, 1999;Tierney, Smerdon, Anchukaitis, & Seager, 2010). Hence, examining the influence of ENSO and IOD on eastern Africa rainfall is vital to improve the understanding of mechanisms affecting regional weather conditions and the extent of global weather teleconnections.…”
Section: Remote Climate Forcing Of Rainfall On the Bluesupporting
confidence: 92%
“…All Pearson correlations were performed using SPSS (IBM, SPSS statistics, 20.0.0). To account for such lag-effects, we characterized the El Niño/positive-IOD and the La Niña/negative-IOD based on 6-month (June-November) averages of SSTs and IOD events (Manatsa & Mukwada, 2012;Trenberth, 1997). Furthermore, ENSO/IOD events generally have an immediate impact on rainfall extremes, but these impacts may not instantaneously be reflected by responses of biological systems (e.g., tree growth), because tree growth varies not only with the amount of rain falling in a given season but may also be affected by growing conditions during previous seasons (Maza-Villalobos, (14) reported that identified rainfall extremes from the reconstructed rainfall just after ENSO/IOD years as the effects of previous year ENSO/IOD events on the UBNRC rainfall patterns.…”
Section: Rainfall Variability Teleconnection-extreme Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Overhanging this region is an intense high pressure anomaly, having the greatest positive anomalies located between 300 and 600 mb (Figure (g)). This strong high pressure anomaly reflects a strengthening of the Botswana Upper High (Manatsa and Mukwada, ) leading to reduced values of relative humidity and wind speed, limited cloud cover, lower PET, curtailed atmospheric water vapour absorption of incoming radiation and suppressed mechanical mixing. Directly below the high pressure anomaly is a region of weak low pressure anomaly located between 21° and 27°S coinciding with the warmest temperature anomalies (Figure (h)) where near surface thermal forcing is largest and associated with strong heating of the land‐surface.…”
Section: Resultsmentioning
confidence: 99%